The Impact of Basel Standards on Default Risk: A Case of Islamic Banks in Bangladesh - Ahmed, Md. Adnan; Mahmud, Imran (Research of Islamic Economics, 2025)
Default risk is a major concern for banks and is shaped by both internal and external factors. Regulatory frameworks like Basel III aim to mitigate such risks. This study investigates the impact of Basel III standards on the default risk of Islamic banks in Bangladesh, focusing on three key indicators: Capital Adequacy Ratio (CAR), Liquidity Coverage Ratio (LCR), and Net Stable Funding Ratio (NSFR). The research covers all Islamic banks in Bangladesh and utilizes secondary data from annual reports. Default risk is assessed using the z-score, where a higher score indicates a lower probability of insolvency. Control variables include credit risk, investment propensity, off-balance sheet exposure, economic growth, and lending rates. A Random Effects Model is employed, with Panel-Corrected Standard Errors (PCSE) applied to address heteroskedasticity, autocorrelation, and cross-sectional dependency. Findings reveal that CAR, LCR, and NSFR significantly reduce default risk, highlighting the effectiveness of Basel III measures in strengthening financial stability. This study uniquely emphasizes Islamic banks and explores the alignment between globally recognized regulatory standards and Sharia-compliant banking. The results offer valuable insights for regulators, policymakers, and bank managers striving to balance regulatory compliance with the principles of Islamic finance.